Rancang Bangun FM Transmitter Menggunakan Metode Spread Spectrum Signal Berbasis Raspberry Pi - Achmad Hanif; Aad Hariyadi; Aisah Aisah (Jurnal Jaringan Telekomunikasi, 2021)
The need for a communication system that can solve interference problems, can guarantee the confidentiality of information sent and can operate at low S / N (Signal to Noise Ratio) levels or is resistant to large noise. One of the technology in communication systems is the spread spectrum system An important characteristic of spread-spectrum communication is that it can provide protection against interfering signals with limited radio communication power using RDS technology and SBC-based spread spectrum which is compatible with spread spectrum technology which requires little power for operation SBC (Raspberry pi) can be implemented into an FM transmitter using the Broadcom bcm 2837 SOC socket which will produce a base clock, then the output signal will be generated via the GPIO 7.